Adolescents’ sleep quality is associated with day of the week, school timing and chronotype - Rodriguez Ferrante, Guadalupe (2024)
Late chronotypes and early school start times are associated with unhealthy sleep habits during adolescence. Here we examine the impact of the relationship between school timing and chronotype on sleep quality in 349 Argentinian high-school students (age: 17-18 y.o., 49% females) randomly assigned to attend school in the morning, afternoon or evening. Students completed the Munich Chronotype Questionnaire and ranked their sleep quality using a Likert-like scale. We found higher sleep quality on free days than on weekdays. Importantly, morning-attending students showed lower sleep quality on weekdays. Finally, the interaction between school timing and chronotype was associated with sleep quality on weekdays: later chronotypes were associated with poorer sleep quality in morning- and afternoon-attending students, but not in the evening. Altogether, our results suggest that attending school in the morning is associated with shorter sleep duration and higher social jetlag, but also with lower sleep quality during adolescence.